Ficção e realidade no jogo literário e obsessivo de Enrique Vila-Matas - Simões, Leilane Hardoim (2024)
This doctoral thesis analyzes the book Aire de Dylan (2013), by Enrique Vila-Matas. Through an approximation with the works of the the Spanish writer that deal with literature more than as a theme, but as a protagonist who is aware and critical of itself. Firstly, we will introduce the writer and his works, bearing in mind that we argue that his writing passes through the sieve of autofiction as the generator of his self-mythography, given that Vila-Matas dilutes the relationship between the real and the fictional in his books, through the discussion of literature itself as an obsession. Next, we'll look at how Vila-Matas uses references and quotations through the concept of Rhizome, by the philosophers Deleuze and Guattari (1995). Quotations and references are part of Vila-Matas's narrative. We will trace the trajectory of the reading carried out for this research of Villamatista works, which assume a self-consciousness in order to understand how literature, as a character and a theme, becomes obsessive. Two books of short stories will be investigated: Suicidios ejemplares (1991) and Chet Baker piensa en su arte: Relatos selectos (2011); and three novels: Historia abreviada de la literatura portátil (1985), Bartleby y compañía (2000) and, finally, Kassel no invita a la lógica (2014a). Through these books we will study the basic work of this research, Aire de Dylan (2013), conducting a reading movement that is justified because we believe that Vilamatista literature is rhizomatic in its referencing, including internally between works, besides configuring as obsessive. Finally, we will bring in Linda Hutcheon and her politics to discuss how irony and, to a lesser extent, humor, transform the way we read the relationship between fiction and reality in Enrique Vila-Matas' obsessive literary play.